ANALISIS SWOT JASA HOTEL - Conie Nopinda Br Sitepu; Lisda Br Hutasoit (JURNAL REGIONOMIC, 2021)
Hotels in Berastagi must win the competition in marketing their products and services. Toincrease market share, companies need to implement a competitive strategy using the SWOTanalysis method which stands for Strengths, Weaknesses, Opportunities, and Threats, throughthis leadership method will be very helpful in formulating a service marketing mix strategy.This needs to be done by the company considering that competition with competingcompanies engaged in business is tight. From the results of the calculation of the IFAS andEFAS matrices that can be used by hotels in Berastagi, namely an aggressive strategy. Withthis strength, hotels in Berastagi can take advantage of existing opportunities. The number ofassessment factors for strengths and weaknesses. Hotels in Berastagi can control the threatsand weaknesses that exist, the hotel in Berastagi will be even better and its vision and missionwill be achieved. This shows that hotels in Berastagi must continue to make efforts to improveproduct quality, facilities, and services